Analysis of the Implementation of Cyber Security in Improving Online Transaction Security - Muhammad Iffan; Vebriani Vonie Zatsiyah (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
Digital transformation in the banking sector has driven an increase in the use of online banking services, but also raised the risk of cyber threats that can disrupt the confidentiality, integrity, and trustworthiness of financial transactions. This study investigates how cybersecurity, viewed from a Management Information Systems (MIS) perspective, can improve digital banking transaction security. A systematic literature review using the PRISMA approach was employed. The method used in this study is a systematic literature review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The article was searched through Google Scholar with the keywords